Implementation of an environmental-based alternative integrative thematic model to increase meaningfulness and learning outcome - Kharisma, Itsna; Mawardi, Mawardi (Universitas Pendidikan Ganesha, 2018)
This study was aimed at improving the meaningfulness and learning outcomes of grade 2 students of SDN Gendongan 02 Tingkir District of Salatiga City by applying an environmental-based alternative integrative thematic design. This study was applied to 39 students as the subject and used Stringer model in 2 cycles with look, think, and act phases. The data collection instruments were test, questionnaires, observation sheets, and field notes. The test instruments were used to determine student learning outcomes. The questionnaire was used to determine the meaningfulness of student learning. While the observation sheet and field notes were used to monitor the course of learning according to the learning scenario. The data analysis technique was descriptive comparative technique. The results show that there is an improvement from cycle I to cycle II, in both meaningfulness and student learning outcomes. Therefore, the environmental-based alternative integrative thematic design can be used to improve learning meaningfulness and student learning outcomes.